ESTIMASI NILAI PASAR WAJAR EKUITAS PTPN XIII DALAM RANGKA INITIAL PUBLIC OFFERING - , Umardani Yusuf Wahyudi; , Prof. Dr. Eduardus Tandelilin, M.B.A., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In strengthening firmâs capital structure and expanding firmâs business, PT Perkebunan Nusantara XIII (PTPN XIII) has conducted a corporate action through initial public offering on Januari 2012. The purpose of this research is to estimate the fair market value of the equity in order to initial public offering. The fair market value in this research is obtained by using discounted cash flow-cash flow to equity model, relative valuation with application of PER (Price to Earning Ratio), PBV (Price to Book Value), PSR (Price to Sales Ratio) multiples and the economic value added method (EVA). The fair market value of PTPN XIII can be used by firm as a reference in determining the share price that will be offered to the public. For this study, the data observed using discounted cash flow-cash flow to equity model, economic value added method and relative valuation method are financial statements and other information contained in the annual report of PTPN XIII for period 2004 to 2010, and financial statements in 2010 of the comparable companies